EKOLOGI HUTAN GAMBUT DITAMAN NASIONAL TANJUNG PUTING, KALIMANTAN TENGAH - Edi Mirmanto; Ruddy Polosakan; Herwint Simbolon (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Ecological studies of peat-swamp forest was conducted in the Tanjung Puting National Park,Central Kalimantan. One-hectare permanent plot has been establishes in order to describe the forest structure and floristic composition. Within 1-ha plot 141 species of tree (dbh >10 cm) and saplings (dbh 5-10 cm) belongs to 84 genera and 43 families recorded. Glutta wallichii, Neoscortechinia philippinensis and Gonystyllus bancanus were dominant tree species, whereas Baccaurea racemosa was very dominant for sapling stage.Tree's density 2 2 was 728 /ha with basal area of 43.01 m /ha whereas density of sapling was 904 /ha with basal area of 3.8 m /ha. Most (30.7 %) of trees with dbh 10 - 30 cm and only 2.23 % of them reach up to dbh > 50 cm. There are three canopy layers that are I-layer was 26.8-33.6 m,II-layer was 17.8-26.8 m and Ill-layer was 9.8-17.6 m high.